Morphological evaluation and variability analysis of Brassica rapa germplasm accessions collected from Uttarakhand Hills - Tabassum; AS Jeena; Arvind Singh Negi; Deepak Kaujalagi (Journal of Oilseed Brassica, 2026)
The present experiment was conducted to estimate genetic variability, heritability and genetic advance among thirtyBrassica rapa germplasm accessions. These accessions were evaluated in randomized block design in two replicationswith three checks to identify genetically diverse accessions for the improvement of yield and other traits in Brassicarapa. Data was recorded on 8 quantitative traits viz., plant height, shoot length, siliqua length, beak length, number ofsiliqua, number of seeds per siliqua, siliqua density and seed yield per plant. Higher values of GCV and PCV wereobserved for seed yield per plant followed by siliqua density, number of seeds per siliqua, beak length and shoot length.Higher GCV indicated stability in the expression of these traits and better transmissibility of the traits from parents to theprogeny. High heritability coupled with high genetic advance as percent of mean was observed for all the traits understudy indicated the predominance of additive gene action in the inheritance of these traits. Therefore, selection wouldbe effective for the improvement of these traits in following generations